Computational thinking in the curricular component of mathematics in basic education: Possibilities and challenges - Reichert, Janice Teresinha; Kist, Milton (International Journal of Trends in Mathematics Education Research, 2023)
This article highlights and discusses aspects of the perceptions of a group of Mathematics teachers in Basic Education about Computational Thinking (CT) and its possibilities of working simultaneously with the curricular component of Mathematics in Basic Education. The case study was carried out through a continuing education course and focused on the application of questionnaires with open questions, as well as on reports on the inclusion of activities, by the participants, in their teaching practice during the course. The responses were analyzed from a qualitative perspective and the results highlight the predominance of lack of knowledge on the subject, especially with regard to the use of methodologies that develop computational thinking associated with specific objects of Mathematics knowledge.